2008
DOI: 10.1007/s11703-008-0070-y
|View full text |Cite
|
Sign up to set email alerts
|

Study on the in vitro culture of cut plants in wheat haploid embryo induction by a wheat × maize cross

Abstract: Study on the in vitro culture of cut plants in wheat haploid embryo induction by a wheat 6 maize cross E Higher Education Press and Springer-Verlag 2008Abstract The wheat 6 maize system is one of the most effective ways to produce haploids in wheat. Whether and how it could be successfully applied in practical breeding mostly depends upon the efficiency of haploid embryo production. To perfect the protocols of haploid embryo induction, the efficiency of haploid embryo production between in vitro culture of cut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
7
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3
1

Relationship

5
3

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 14 publications
3
7
0
1
Order By: Relevance
“…Variance analysis showed that there were significant difference in embryo rate (P=0.00) and haploid seedling rate (P=0.00) among different combinations, which indicated that embryo rate and haploid seedling rate were more susceptible to genotypic influence. The averages of embryo rate, seedling rate of embryos and chromosome doubling rate of seedlings were 36.76%, 62.65% and 86.42% respectively, exhibiting good efficiency in DH production as showed in our previous study [22]. Figure 1), which facilitates mass production of wheat DHs by wheat ´ maize crosses because plenty of fresh pollens are available from naturally and repeatedly planted maize plants from late April to early November [22][23][24][25][26].…”
Section: Production Of Dh Linessupporting
confidence: 76%
See 1 more Smart Citation
“…Variance analysis showed that there were significant difference in embryo rate (P=0.00) and haploid seedling rate (P=0.00) among different combinations, which indicated that embryo rate and haploid seedling rate were more susceptible to genotypic influence. The averages of embryo rate, seedling rate of embryos and chromosome doubling rate of seedlings were 36.76%, 62.65% and 86.42% respectively, exhibiting good efficiency in DH production as showed in our previous study [22]. Figure 1), which facilitates mass production of wheat DHs by wheat ´ maize crosses because plenty of fresh pollens are available from naturally and repeatedly planted maize plants from late April to early November [22][23][24][25][26].…”
Section: Production Of Dh Linessupporting
confidence: 76%
“…For DH production, an improved protocol [22,23] was adopted. Wheat spikes were pollinated with fresh maize pollen 24 to 48 hours after emasculation.…”
Section: Methods Of Producing Dhsmentioning
confidence: 99%
“…of seedlings germinated from every 100 inoculated embryos, P=0.00) among different combinations, suggesting that embryo rate and haploid seedling rate were more susceptible to genotypes. The averages of embryo rate, seedling rate of embryos and chromosome doubling rate of seedlings were 36.76%, 62.65% and 86.42% respectively, exhibiting a good efficiency in DH production as demonstrated in our previous studies [25][26][27][28][29]. Temperate climate at Kunming, especially from May to October, allows planting spring and vernalized winter wheat materials throughout the year under natural condition ( Fig.…”
Section: Production Of Dh Linessupporting
confidence: 60%
“…The bulbosum method-using in order to induce the elimination of paternal chromosomes of embryo cells has been applied to several species, such as Hordeum vulgare L., after crossing with H. bulbosum L. A process of elimination of bulbous barley chromosomes was observed in hybrid embryos (Kasha and Kao 1970). Haploid embryos were also obtained after crossing wheat and maize (Gu et al 2008). 4.…”
Section: Introductionmentioning
confidence: 99%